L’estetica dell’impossibile: lo strano caso del gotico e della fantascienza - Federica Perazzini (Between, 2019)
In the history of human creativity, the act of imagining the impossible has always been at the core of the physical and metaphysical perception of the unknown. The scholarly debate regarding the nature of the impossible gained particular relevance in the context of British Enlightenment when the expanding sciences, along with literature, attempted to provide empirical validation to inexplicable and supernatural phenomena. In this way, the discrepancies between the overlapping ontologies of the Age of Faith and the Age of Reason became apparent as the ancestral literary practice of the fantastic merged with the rising genre of the novel. The assimilation of the conventional tropes of supernatural literature within the narrative frame of formal realism led to the development of two fortunate sub-genres: the Gothic and Science Fiction. The former evolved around the mutual disruption of the empirically-based conception of reality and the transgression of the moral code implied in the construction of civic order. The latter derived from the relocation of specific gothic features into a larger dimension of social anxiety concerning the abuses of reason concealed as a path towards common good and future progress.